Sensing justice through contemporary Spanish cinema : aesthetics, politics, law - López Lerma, Mónica (Edinburgh critical studies in law, literature and the humanities., 2021)
Sensing Justice examines the aesthetic frames that mediate the sensory perception and signification of law and justice in the context of 21st century Spain. What senses do these frames privilege or downgrade? What kind of subjects do they show, construct, and address? What kind of affective and ethical responses do they invite? What kind of judgments do they invite? By creating new frames of perception and signification, the films analyzed challenge the senses of law and justice traditionally taken for granted and reconfigure them anew. Engaging with legal theory, film studies, aesthetics, and politics, Sensing Justice provides a compelling illustration of how law and justice are multisensory and embodied experiences.